2018
DOI: 10.18632/oncotarget.24172
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and prognostic significance of C-reactive protein/albumin ratio in patients with solid tumors: an updated systemic review and meta-analysis

Abstract: C-reactive protein/albumin ratio (CAR) was originally used as a novel inflammation-based prognostic score in predicting outcomes in septic patients. Recently, more and more studies have reported the prognostic value of pretreatment CAR in solid tumors. However, the results remain controversial rather than conclusive. We conducted a meta-analysis based on 24 studies with 10203 patients to explore the relationship between CAR and survival outcomes in patients with solid tumors. The correlation between CAR and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 59 publications
2
34
1
Order By: Relevance
“…Pre-operative biomarker values were similar in females and males, however, after surgery, females showed a more significant decrease in NLR. A recent meta-analysis suggested that an elevated CAR was indicative, not only of sepsis, but also of unfavorable clinico-pathological findings in solid tumors [16]. In the present study, although unchanged after surgery, CAR values were nearly three times higher in the bigger tumor size group.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Pre-operative biomarker values were similar in females and males, however, after surgery, females showed a more significant decrease in NLR. A recent meta-analysis suggested that an elevated CAR was indicative, not only of sepsis, but also of unfavorable clinico-pathological findings in solid tumors [16]. In the present study, although unchanged after surgery, CAR values were nearly three times higher in the bigger tumor size group.…”
Section: Discussioncontrasting
confidence: 56%
“…C-reactive protein/serum albumin ratio (CAR): Defined as the ratio of CRP to serum albumin as a prognostic value of pretreatment in solid tumors [16].…”
Section: Definitions and Calculationsmentioning
confidence: 99%
“…Previous meta-analyses assessed some of these relationships and revealed that the systemic inflammatory markers had predictive value for OS of GC patients [ 75 77 ]. However, none of the three markers have been linked to the GC survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Both CAR and GPS have been considered as independent risk factors for the prognosis of various tumors. 36 , 37 However, since the relationship between CAR and bladder cancer remains unclear, the investigators attempted to combine CRP with albumin to form a new prognostic factor in bladder cancer after RC.…”
Section: Discussionmentioning
confidence: 99%